'Dashing about with the greatest gallantry': polo in India and the British metropole, 1862–1914. Issue 1 (2nd January 2020) - Elsaesser, Luise
ABSTRACT: The period from 1870 to the Great War was defined by a new and more intensive phase of imperialism. Following previous debates initiated by scholars such as MacKenzie, Burton, or Bayly this article analyses the impact of Empire on the metropole. In suggesting that the imperial space was not a one-way street, the paper is going beyond Said's orientalist approach. This argument uses the example of the Indian game of polo. Unlike most imperial sports, polo was adapted by the British from their colonial subjects, creating the opportunity of a common cultural space. How did polo influence socio-cultural and political power constellations in India and the metropole? The paper will provide nuance on regional contexts and the effects of sport on specific groups. Unpacking the resulting interdependencies, ambivalences, and the mutability of polo in the British imperial self-image, the paper does not neglect Indian agency. Polo showcases an interrelation of ideas and beliefs which are used to understand the respective environment as well as the internationalisation of sport. Researching sport in an imperial context and its interactions on a local and transnational level can thus display rising asymmetries of political, cultural, and social agencies in a global process.